Effect of different beverages and storage period on bis-acryl color stability using two assessment methods - Bastos, Natália A.; Bitencourt, Sandro B. [UNESP]; de Mello, Igor P.; de Abreu, Celina W.; Bombonatti, Juliana F.S.; Silva, Mariana M. (Wiley, 2020)
Objective: This study aimed to evaluate the color stability (ΔE00) of bis-acryl resins after different immersion solutions and storage time by different evaluation methods. Materials and methods: Sixty specimens (n = 30) were prepared from Protemp 4 and Structur 3. The specimens were divided into three groups (n = 10), according to the immersion solution (artificial saliva, cola beverage, and yerba mate tea) and evaluated at two storage times (7 and 14 days). The ΔE00 of each group was calculated using color coordinates obtained by a spectrophotometer and by a digital method, using the CIEDE2000 color difference formula. Data were analyzed by three-way ANOVA and Tukey test (α = 0.05). Results: The 7-day period presented the lowest ΔE00 values, regardless of the material and solution evaluated for both evaluation methods (ΔE00 < 0.93; ΔE00 < 3.12). The immersion solution with the highest color change was yerba mate tea after 14 days (ΔE00 > 2.11). For digital analyses, all materials and solutions at both times presented ΔE00 values higher than the clinically acceptable (ΔE00 > 1.8), while in spectrophotometer only in yerba mate tea (14 days) Structur was above the clinical acceptability level. Conclusions: Yerba mate tea was the immersion solution with a higher color change in both materials and assessment methods. The highest values were found after 14 days of immersion, regardless of the solution. The ΔE00 for the digital method was higher than the spectrophotometer analysis. Clinical significance: It is important to identify the influence of staining beverages on interim materials used in patients requiring temporary rehabilitation. The use of a spectrophotometer seems to be more accurate than the digital method for the evaluation of color parameters of the tested materials.
Keywords: color science; dental materials; laboratory technology; operative dentistry; prosthodontics